2013
DOI: 10.1093/cid/cit335
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino-Acid Change in a Highly Conserved Motif of gp41 Elicits HIV-1 Neutralization and Protects Against CD4 Depletion

Abstract: These findings suggest that a specific substitution in a 3S-based immunogen might allow the generation of specific antibodies, providing a foundation for a rational vaccine that combine a capacity to neutralize HIV-1 and to protect CD4(+) T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 36 publications
4
28
1
4
Order By: Relevance
“…This region has also been identified to be the target of various other antibody-mediated activities (42)(43)(44)(45)(46)(47)(48)(49)(50). Recent three-dimensional studies of gp140 trimers by crystallography and high-resolution cryo-electron microscopy show that this region lies in close proximity to the plasma membrane (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…This region has also been identified to be the target of various other antibody-mediated activities (42)(43)(44)(45)(46)(47)(48)(49)(50). Recent three-dimensional studies of gp140 trimers by crystallography and high-resolution cryo-electron microscopy show that this region lies in close proximity to the plasma membrane (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…An alanine-scanning assay within the 3S motif of the viral gp41 protein showed that a tryptophan residue at position 614 (W614) is crucial for the virus entry ( Petitdemange et al, 2013 ). The main reason could be that this region plays a key role in the formation of the six-helix bundled gp41 ectodomain core structure that imposes several kinetic and steric constraints responsible for the high degree of motif preservation, as previously reported ( Gallo et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these data could explain the absence of detectable “3S” escape variants, and the remarkable conservation of the 3S motif within the gp41 ( Vieillard et al, 2005 , Potard et al, 2013 ). Next, we generated in mice a class of Abs against the 3S motif, called W614A-3S Ab that elicits neutralizing activity, against a panel of tier 1 and tier 2 viruses from clades A, B, C and E ( Petitdemange et al, 2013 ). More recently, these data were confirmed in rabbit and macaque models (unpublished data are from Vieillard et al).…”
Section: Introductionmentioning
confidence: 99%
“…At this time, it is not clear how much divergence in antibody epitopes is needed to escape from herd immunity. Studies with GII.4 human NoV, mouse NoV, and other RNA viruses have demonstrated significant changes in blockade or neutralization potential with only a single amino acid change (34,(49)(50)(51). It is possible that with an expanded panel of GII.2 blockade MAbs, we may have been able to more clearly antigenically differentiate the GII.2 VLPs.…”
Section: Discussionmentioning
confidence: 99%